Before Kukulkán Bioarchaeology of Maya Life, Death, and Identity at Classic Period Yaxuná - Ardren, Traci (University of Arizona Press, 2017)
This volume illuminates human lifeways in the northern Maya lowlands prior to the rise of Chichén Itzá. This period and area have been poorly understood on their own terms, obscured by scholarly focus on the central lowland Maya kingdoms. "Before Kukulkán" is anchored in three decades of interdisciplinary research at the Classic Maya capital of Yaxuná, located at a contentious crossroads of the northern Maya lowlands.Using bioarchaeology, mortuary archaeology, and culturally sensitive mainstream archaeology, the authors create an in-depth regional understanding while also laying out broader ways of learning about the Maya past. Part 1 examines ancient lifeways among the Maya at Yaxuná, while part 2 explores different meanings of dying and cycling at the settlement and beyond: ancestral practices, royal entombment and desecration, and human sacrifice. The authors close with a discussion of the last years of occupation at Yaxuná and the role of Chichén Itzá in the abandonment of this urban center."Before Kukulkán" provides a cohesive synthesis of the evolving roles and collective identities of locals and foreigners at the settlement and their involvement in the region's trajectory. Theoretically informed and contextualized discussions offer unique glimpses of everyday life and death in the socially fluid Maya city. These findings, in conjunction with other documented series of skeletal remains from this region, provide a nuanced picture of the social and biocultural dynamics that operated successfully for centuries before the arrival of the Itzá.